European-Led Climate Policy Versus Global Mitigation Action. Implications on Trade, Technology, and Energy - Enrica De Cian; Ilkka Keppo; Johannes Bollen; Samuel Carrara; Hannah Förster; Michael Hübler; Amit Kanudia; Sergey Paltsev; Ronald Sands; Katja Schumacher (Fondazione Eni Enrico Mattei (FEEM), 2014)
This paper examines how changes in an international climate regime would affect the European decarbonization strategy and costs through the mechanisms of trade, technology, and innovation. We present the results from the Energy Modeling Forum (EMF) model comparison study on European climate policy to 2050. Moving from a no-policy scenario to an existing-policies case reduces all energy imports, on average. Introducing a more stringent climate policy target for the EU only leads to slightly greater global emission reductions. Consumers and producers in Europe bear most of the additional burden and inevitably face some economic losses. More ambitious mitigation action outside Europe, especially when paired with a well-operating global carbon market, could reduce the burden for Europe significantly. Because of global learning, the costs of wind and especially solar-PV in Europe would decline below the levels observed in the existing-policy case and increased R&D spending outside the EU would leverage EU R&D investments as well.
Keywords: Q5; Q54; 330; Climate Change; Stabilization Policy; International Participation